2005
DOI: 10.1021/jf050306v
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of the Potato Cysteine Protease Inhibitor Group (Cv. Elkana)

Abstract: The conformational stability of potato cysteine protease inhibitor (PCPI), the second most abundant protease inhibitor group in potato tuber, was investigated at ambient temperature and upon heating using far- and near-UV circular dichroism spectroscopy, fluorescence spectroscopy, and differential scanning calorimetry (DSC). The PCPI isoforms investigated have a highly similar structure at both the secondary and the tertiary level. PCPI isoforms show structural properties similar to those of the potato serine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
(42 reference statements)
2
9
0
2
Order By: Relevance
“…It has been shown that a-helical parts of patatin unfold in the 45-55 C region, whereas the b-stranded parts unfold more gradually from 50 to 90 C (Pots, de Jongh, Gruppen, Hamer, & Voragen, 1998). The heat-induced conformational changes of the two main protease inhibitor groups, PSPI and PCPI, have also been investigated previously Pouvreau, Kroef, et al, 2005). The authors reported T-max around 62-67 C for the two protease inhibitor groups, which corresponds well with the Tmax of concentrate B.…”
Section: Heat-induced Unfoldingmentioning
confidence: 73%
See 1 more Smart Citation
“…It has been shown that a-helical parts of patatin unfold in the 45-55 C region, whereas the b-stranded parts unfold more gradually from 50 to 90 C (Pots, de Jongh, Gruppen, Hamer, & Voragen, 1998). The heat-induced conformational changes of the two main protease inhibitor groups, PSPI and PCPI, have also been investigated previously Pouvreau, Kroef, et al, 2005). The authors reported T-max around 62-67 C for the two protease inhibitor groups, which corresponds well with the Tmax of concentrate B.…”
Section: Heat-induced Unfoldingmentioning
confidence: 73%
“…Protease inhibitors (5-25 kDa) with pI's between 5.1 and 9.0 (Pouvreau et al, 2001) and other proteins of higher molecular weights make up the other major proteins (Pots et al, 1999). The two major groups of protease inhibitors are the potato serine protease inhibitors (PSPI) and the potato cystein protease inhibitors (PCPI) with molecular masses of 20.5 and 21.0, respectively Pouvreau, Kroef, et al, 2005). Potato proteins are well balanced in their amino acid composition, comparable to milk and egg protein (Knorr, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Pineapple juice bromelain is active in acidic pH, with an optimum pH range of between 4 and 6 ( Figure 3C). For the bromelain inhibition ( Figure 3D), we used the juice of potato tubers that is rich in potato cysteine proteinase inhibitor, PCPI [27].…”
Section: Using 3d Graphical Representation Of Enzyme Propertiesmentioning
confidence: 99%
“…Proteaz inhibitörleri, besin sindirimini engelleme özelliklerinin yanı sıra anti-kanserojen etki ve kolesitokinin oluşturma potansiyeline de sahiptirler. Sahip oldukları di-sülfit bağlarının koruyucu etkileri sayesinde pH 3,0-7,5 aralığında üç boyutlu yapılarında herhangi bir değişim gözlenmez [24].…”
Section: Proteaz İnhibitörüunclassified